2001
DOI: 10.1089/10766290152045057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics ofnimGenes Encoding 5-Nitroimidazole Resistance amongBacteroidesStrains Isolated in Morocco

Abstract: We report here an evaluation of the dissemination of nim genes, encoding 5-nitroimidazoles resistance, among Bacteroides clinical strains isolated in Morocco. This study was done using a PCR method. Among 60 strains studied, nine contain a copy of a nim gene. The sequence determination of these genes showed that they are homologous to three nim genes previously characterized in strains isolated in France: nimB (five genes), nimC (three genes), and nimA (one gene). Although the nimA and nimC genes were previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Exceptions to this main rule were observed (Tables 1 and 2), verifying our initial approach. The above results are in agreement with the findings of Haggoud et al, 18 who demonstrated that nimA and nimC genes could be chromosomal. Another important issue regarding the nim gene IS element connection is the degree of gene activation.…”
Section: Localization Of Nim Genes and Determination Of The Activatinsupporting
confidence: 93%
See 1 more Smart Citation
“…Exceptions to this main rule were observed (Tables 1 and 2), verifying our initial approach. The above results are in agreement with the findings of Haggoud et al, 18 who demonstrated that nimA and nimC genes could be chromosomal. Another important issue regarding the nim gene IS element connection is the degree of gene activation.…”
Section: Localization Of Nim Genes and Determination Of The Activatinsupporting
confidence: 93%
“…[14][15][16][17] The nimA and nimC genes have also been found chromosomally. 18 The molecular action of a nim nitroimidazole reductase protein of Deinococcus radiodurans has recently been deduced from crystallographic data suggesting a reaction mechanism involving the 2-electron reduction of metronidazole, preventing accumulation of the toxic nitro radical, and an important role for His-71 residue. 19 The aim of the present study was to examine the genetic background of metronidazole-resistant Bacteroides strains with respect to the nim gene type, the location of the genes on known or novel plasmids or on chromosomes and demonstration of the activating IS element type.…”
Section: Introductionmentioning
confidence: 99%
“…The nimA and nimC were ®rst detected on plasmids, but are now also located on chromosome, which indicate an exchange of nim genes between plasmids and chromosome. The clinical signi®cance of Bacteroides strains with reduced susceptibility to metronidazole has not yet been investigated, and no therapeutic failures are described.`Silent' nim genes have been detected in Bacteroides strains with MICs of 0.5±2 mg/L [28]. It is important to be aware of this, because activation of silent resistance genes by promoters located on IS-elements exists in Bacteroides species [22,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to nimB that is prevalent among the MTZ-resistant Bacteroides spp. isolated in Morocco [18] and South Africa [27] and nimA in a series from the UK [20].…”
Section: Discussionmentioning
confidence: 99%